2021
DOI: 10.1108/meq-08-2021-0187
|View full text |Cite
|
Sign up to set email alerts
|

How can environment get better? A research review of pollution governance

Abstract: PurposeThis study aims to build a global environmental quality protection convention to jointly address the problems of environmental pollution governance worldwide.Design/methodology/approachFrom the perspective of environmental pollution of the air, ocean, forest, water and solid waste, the authors summarize the main important measures and mechanisms of environmental pollution governance in various countries.FindingsThe results indicate that management research on biodiversity and natural resources must be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Our models have not explicitly tested the EKC hypothesis, but we have included economic development among the independent variables in both GHG emissions and CI driving factors estimates. The results confirmed that economic development is a major contributor to pollution in our global panel of countries, in line with vast research on the topic, including works on the validity of the EKC-see, for example, the excellent review papers of Ali & de Oliveira (2018), He, et al (2022), and Mardani, et al (2019. Switching from fossil fuels to nuclear and renewable energy sources, on the other hand, increases the likelihood of mitigating this negative link between development and environmental degradation.…”
Section: Discussionsupporting
confidence: 85%
“…Our models have not explicitly tested the EKC hypothesis, but we have included economic development among the independent variables in both GHG emissions and CI driving factors estimates. The results confirmed that economic development is a major contributor to pollution in our global panel of countries, in line with vast research on the topic, including works on the validity of the EKC-see, for example, the excellent review papers of Ali & de Oliveira (2018), He, et al (2022), and Mardani, et al (2019. Switching from fossil fuels to nuclear and renewable energy sources, on the other hand, increases the likelihood of mitigating this negative link between development and environmental degradation.…”
Section: Discussionsupporting
confidence: 85%
“…The environmental impact assessment (EIA) report is fast becoming a key approach used for identifying, preventing, minimising and compensating for any unfavourable impacts on the environment. A typical example of such an unfavourable impact is the deterioration of environmental quality caused by development of industries (He et al, 2022). Zhu (2018) found that EIA promotes free will of public involvement as well as freedom of the project-related information.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the governance attaches great importance to industrial wastewater pollution. To improve the environmental quality of industrial wastewater, China has intensified the governance of industrial wastewater pollution, and the current work on environmental rule of law and environmental protection has made progress [ 6 ]. General Secretary Jinping Xi pointed out in his nineteenth important report that we should speed up the construction of ecological civilization and promote green development [ 7 ].…”
Section: Introductionmentioning
confidence: 99%